2016
DOI: 10.1186/s13063-016-1528-5
|View full text |Cite
|
Sign up to set email alerts
|

Standardised Outcomes in Nephrology—Children and Adolescents (SONG-Kids): a protocol for establishing a core outcome set for children with chronic kidney disease

Abstract: BackgroundChildren with chronic kidney disease (CKD), requiring dialysis or kidney transplantation, have a mortality rate of up to 30-fold higher than the general aged-matched population, and severely impaired quality of life. Symptoms such as fatigue and pain are prevalent and debilitating. Children with CKD are at risk of cognitive impairment, and poorer educational, vocational, and psychosocial outcomes compared with their well peers, which have consequences through to adulthood. Treatment regimens for chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 57 publications
2
25
0
1
Order By: Relevance
“…The outcomes identified in this study will inform the development of a core outcome set through the SONG-Kids Initiative . 24…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcomes identified in this study will inform the development of a core outcome set through the SONG-Kids Initiative . 24…”
Section: Discussionmentioning
confidence: 99%
“…14 Prior studies have systematically identified outcomes that are important to adults with CKD, 21,22 but the outcomes that are highly prioritized by children with CKD and caregivers are unknown. 23,24 This study aims to identify outcomes that are important to children across all stages of CKD, and their caregivers, and the reasons for their prioritization. This may inform the choice of research outcomes to inform patient-centered decision-making in CKD care.…”
Section: Introductionmentioning
confidence: 99%
“…The Standardised Outcomes in Nephrology (SONG) initiative aims to establish core outcome domains and outcome measures across the full spectrum of chronic kidney disease, with the streams SONG-HD (haemodialysis),(42) SONG-Tx (kidney transplantation),(43) and SONG-Kids (children and adolescents)(44) currently underway. The specific aims of SONG-PD are to: 1) describe the scope, quality, and consistency of outcomes used in PD trials; 2) identify outcomes that are important to patients and caregivers; 3) ascertain health professional attitudes, values, and beliefs regarding outcomes for PD trials; 4) generate a consensus-based prioritised list of core outcome domains; and 5) establish a set of core outcome domains for trials conducted in people on PD.…”
Section: Introductionmentioning
confidence: 99%
“…The study endeavoured to comply with the COnsolidated Criteria for REporting Qualitative Research (COREQ) [27]. The original intent was for this research to adopt a multimethod approach which combined several methods to collect information on a given topic [28]. A combination of focus groups (with the nominal group technique) [29] and semi-structured face to face or phone interviews were used to collect data from eyecare professionals.…”
Section: Methodsmentioning
confidence: 99%
“…Strengths of this study include the mixed methods approach that allowed triangulation of the data and enabled the participants to express concerns in their own words, the involvement of primary and secondary eyecare professionals, and the use of nominal group technique which allowed quantification of barriers and enablers. The concurrent use of an explorative and consensus-oriented method allowed both qualitative and semi-quantitative data to be collected, inform and complement each other but the lack of ophthalmology involvement in the focus group aspect of this research is a limitation [28]. These strategies are known to be helpful when trying to understand complex behaviours and characterise knowledge, attitudes, and barriers of diverse stakeholder groups [30,58,59].…”
Section: Strengths and Limitationsmentioning
confidence: 99%